Exploring the Use of Active Learning Methods in Physical Education to Increase Student Engagement - Febrianto, Gigih Latianda (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the use of active learning and in the context of Classroom Action Research (CAR) in Physical Education (Penjas) subjects to increase student involvement. The low participation of students in Penjas learning activities is the main background for it. This study applies a qualitative strategy with a CAR pattern that applies two cycles. The subjects in this study were grade X students at one of the State Senior High Schools in Madiun. Data were collected through observation, interviews, and documentation, which were analyzed descriptively qualitatively. The results of the study showed that the application of active learning methods, such as group discussions, cooperative games, and guided reflection, were able to increase student enthusiasm and participation in the learning process. In each cycle, increased participation was seen from the increasing number of students who actively asked questions, worked together in groups, and showed interest in participating in each activity given. Teachers also greatly benefit from using this method to improve their ability to manage the class and develop learning strategies that are responsive to student needs. These findings indicate that the implementation of active learning integrated into CAR can create a more participatory and enjoyable learning environment. Thus, this study suggests that physical education teachers should apply active learning methods more frequently as part of continuous improvement in the teaching and learning process, especially in increasing overall student engagement.